2022
DOI: 10.1136/gutjnl-2021-324994
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles from Pancreatic Cancer Stem Cells Lead an Intratumor Communication Network (EVNet) to fuel tumour progression

Abstract: ObjectiveIntratumor heterogeneity drives cancer progression and therapy resistance. However, it has yet to be determined whether and how subpopulations of cancer cells interact and how this interaction affects the tumour.DesignWe have studied the spontaneous flow of extracellular vesicles (EVs) between subpopulations of cancer cells: cancer stem cells (CSC) and non-stem cancer cells (NSCC). To determine the biological significance of the most frequent communication route, we used pancreatic ductal adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 84 publications
(152 reference statements)
3
57
0
Order By: Relevance
“…A recent study used first-degree genetic labeling of tEV-targeted cells and focused on tumor cell-to-tumor cell signaling via EVs. 54 The Authors uncovered an effective cooperation network mediated by tEVs and led by CSC, suggesting that a similar network may be in place between CSC and immune cells. Given the importance of CSC in cancer biology 19 , new technologies that allow to dissect the influence of native tEVs CSC are necessary.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study used first-degree genetic labeling of tEV-targeted cells and focused on tumor cell-to-tumor cell signaling via EVs. 54 The Authors uncovered an effective cooperation network mediated by tEVs and led by CSC, suggesting that a similar network may be in place between CSC and immune cells. Given the importance of CSC in cancer biology 19 , new technologies that allow to dissect the influence of native tEVs CSC are necessary.…”
Section: Discussionmentioning
confidence: 96%
“…Functionally, the EVs have also been demonstrated as key mediators to establish molecular cross-talk between cancer cells and various types of cellular components within the tumor microenvironment (TME) for promoting tumorigenesis by delivering their cargos 38 . EVs have been shown to promote growth, angiogenesis, migration, invasion, and chemoresistance in PDACs 18 , 39 , 40 . Tang et al have demonstrated that exosomes isolated from PDAC patients promote the proliferation, migration, and invasion of MiaPaCa-2 and AsPC-1 cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a role of tumor-derived EVs in premetastatic niche formation and immune suppression has been reported in PDAC 49 . In several reports, EV composition has also been studied to understand their roles in disease pathobiology 39 , 50 , 51 . Along the same lines, the presence of both genomic and mtDNA in EVs has also been reported 38 , 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGRN has been shown to contribute to EMT in liver and pancreatic cancer [ 90 , 91 , 92 ]. In hepatocellular carcinoma (HCC) cells, AGRN is overexpressed and secreted in high levels compared with non-tumor liver cells.…”
Section: Proteoglycans As Regulators Of Emt and Cell Stemnessmentioning
confidence: 99%